Differentiated impacts of image samples on creative performance in cultural tourism product design - Wei, Lun; Wu, Hui; Yu, Mingzhu; Qin, Xuan; Zhang, Wenpei (Frontiers in Communication, 2025)
PurposeCreativity plays a pivotal role in the design of cultural tourism products. This study investigates the impact of different types of image samples on enhancing the creative performance in cultural tourism product design, and and clarifies the practical role of image samples in design inspiration.MethodsA total of 66 design students were recruited and randomly assigned to three groups of 22 each. The samples of cultural tourism product design were categorized into three types: historical site, local culture and natural landscape. Each group was tasked with designing a cultural tourism product based on different samples (historical site, local culture and natural landscape). The design process was divided into three stages, corresponding to three dimensions of creativity and the related seven assessment indicators: idea generation stage—divergent thinking (fluency and flexibility indicators), idea aggregation stage—convergent thinking (adaptability and feasibility indicators), and final design performance stage—design creativity (novelty, aesthetic and practicality indicators).ResultsThe results indicate that historical site and local culture samples significantly contribute to stage 1—divergent thinking (on fluency and flexibility indicators, respectively), while natural landscape contributes to stage 3–design creativity (on both novelty and aesthetics indicators).ConclusionThis study reveals the unique role of image samples in the cultural tourism product design process and emphasizes the necessity of selecting samples based on design stages or creativity dimensions. These findings inform teaching practices, optimizing students’ innovation and cultural expression skills.